Analysis Training and Human Resource Development in PT Bank Central Asia Tbk Office Branch Main Sumedang - Kisthi Hanila Dewi; Dewi Puspasari; Desan Henriawan (West Science Interdisciplinary Studies, 2025)
Study This aiming for describe training and development of human resources human resources at PT Bank Central Asia Tbk Main Branch Office Sumedang. This study uses qualitative research methods through in-depth interviews. The results of the study indicate that PT Bank Central Asia Tbk Main Branch Office Sumedang has implemented human resource training in accordance with the training stages. The methods used in human resource training are on the job training, in class training, e-learning, and out bound. While human resource development is used to develop an employee's career through panel techniques.